How Autophagy Shapes the Tumor Microenvironment in Ovarian Cancer - Ferraresi, Alessandra; Girone, Carlo; Esposito, Andrea; Vidoni, Chiara; Vallino, Letizia; Secomandi, Eleonora; Dhanasekaran, Danny N.; Isidoro, Ciro (Frontiers in Oncology, 2020)
Ovarian cancer (OC) is characterized by a high mortality rate due to late diagnosis and elevated metastatic potential. Autophagy, a lysosomal-driven catabolic process, contributes to the macromolecular turnover, cell homeostasis and survival, and as such it represents a pathway targetable for anti-cancer therapies. It is now recognized that the vascularization and the cellular composition of the tumor microenvironment influence the development and progression of OC by controlling the availability of nutrients, oxygen, growth factors and inflammatory and immune-regulatory soluble factors that ultimately impinge on autophagy regulation in cancer cells. An increasing body of evidence indicates that OC carcinogenesis is associated, at least in the early stages, to insufficient autophagy. On the other hand, when the tumor is already established, autophagy activation provides a survival advantage to the cancer cells that face metabolic stress and protects from the macromolecules and organelles damages induced by chemo- and radiotherapy. Additionally, upregulation of autophagy may lead cancer cells to a non-proliferative dormant state that protects the cells from toxic injuries while preserving their stem-like properties. Further to complicate the picture, autophagy is deregulated also in stromal cells. Thus, changes in the tumor microenvironment reflect on the metabolic crosstalk between cancer and stromal cells impacting on their autophagy levels and, consequently, on cancer progression. Here, we present a brief overview of the role of autophagy in OC hallmarks, including tumor dormancy, chemoresistance, metastasis and cell metabolism, with an emphasis on the bidirectional metabolic crosstalk between cancer cells and stromal cells in shaping the OC microenvironment.